INNOVATION TYPES AND SALES GROWTH IN SMALL FIRMS EVIDENCE FROM KOSOVO (The South East European Journal of Economics and Business, 2020)
The purpose of this paper is to investigate the impact of different forms of innovation on firm growth, in terms of sales. A total of 278 samples were collected from SMEs in the manufacturing, service and trade industries throughout Kosovo. The data were analysed using a logistic regression analysis. The findings confirm the hypotheses that marketing innovation is positively associated with firm growth, while new to the firm products is negatively associated with firm growth. Other innovation attributes have resulted with non-significance value. The findings in this study can be useful for theoretical discussion, as well as for policy formulation related to introduction of innovation and SMEs development considering that innovation is critical factor in today’s market and competition. Further studies should look into how SMEs could investigate over time from the initial stage to the full development of innovation.